The impact of national energy structure on the concentrations, environmental behavior, and sources of polycyclic aromatic hydrocarbons in riverine and coastal sediments of the Beibu Gulf, China. (November 2021) - Han, Minwei; Kang, Yaru; Wang, Weiquan; Liu, Fang; Pei, Jiying; Wang, Yinghui; Zhang, Ruijie; Yu, Kefu
Abstract: In this study, polycyclic aromatic hydrocarbons (PAHs) were measured in sediments of the Beibu Gulf in 2017 to investigate sources and a risk assessment. The results showed the total PAH concentration (∑16 PAHs) in sediments of the Beibu Gulf in 2017 (17.6 ± 16.7 ng g −1 ) was significantly lower than that in 2010 (47.8 ± 27.4 ng g −1 ). The ∑16 PAHs concentrations varied spatially within the Beibu Gulf, impacted by point source pollution. The results of adsorption/desorption and water-air partitioning suggest that the environmental behavior of PAHs in the Beibu Gulf is affected by atmospheric deposition and sediment-water partitioning. A risk assessment showed that the PAHs in sediments were within a safety threshold. Three source apportionment methods show that oil spills and oil and biomass burning were the most important (>83.8%) sources of PAHs in sediments of the Beibu Gulf. Graphical abstract: Unlabelled Image Highlights: First comprehensive investigation of PAHs level in sediments of Beibu Gulf, China Adsorption/desorption process of PAHs between sediment and water was revealed. Environmental behavior of PAHs in water, atmosphere and sediment was discussed. With the transformation of energy structure, PAHs in sediment are greatly reduced. Risk assessment and source apportionment of PAHs were done by various methods.